The Potential of Kampung Silat as a Sports Tourism Destination in West Java - Muhamad Rapli; Tatang Muhtar; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2024)
This research aims to dig up information from various sources. Kampung Silat, as a sports tourism destination, has great potential which can positively impact the progress of Pencak Silat in the region, especially in West Java and the country as a whole. Having a Kampung Silat as a sports tourism destination can provide an excellent opportunity, which, if realized, will impact residents in the progress of pencak silat in the region, especially in Indonesia. This research uses a qualitative method with a descriptive approach. Through observation, interviews, and documentation, data processing was done using NVivo 12 software, then analyzed again using MSPDM (Marketability, Sustainability, Participatory, and Disaster Mitigation) and Culture. The results of research on Word Frequency Query, the word that often appears is “silat”, which is dominated by conversations from sources with a frequency of 3.55% of all data, then followed by the phrase “pencak”, “activity”, “society”, and “sport”. Based on the analysis of researchers referring to MSPDM (Marketability, Sustainability, Participatory, Disaster Mitigation) and Culture, the West Java Province Pencak Silat Center has great potential to become a Kampung Silat as a sports tourism destination.